Presynaptic inhibition upon CB1 or mGlu2/3 receptor activation requires ERK/MAPK phosphorylation of Munc18‐1. (7th April 2016) - Schmitz, Sabine K; King, Cillian; Kortleven, Christian; Huson, Vincent; Kroon, Tim; Kevenaar, Josta T; Schut, Desiree; Saarloos, Ingrid; Hoetjes, Joost P; de Wit, Heidi; Stiedl, Oliver; Spijker, Sabine; et al.
Abstract: Presynaptic cannabinoid (CB1R) and metabotropic glutamate receptors (mGluR2/3) regulate synaptic strength by inhibiting secretion. Here, we reveal a presynaptic inhibitory pathway activated by extracellular signal‐regulated kinase (ERK) that mediates CB1R‐ and mGluR2/3‐induced secretion inhibition. This pathway is triggered by a variety of events, from foot shock‐induced stress to intense neuronal activity, and induces phosphorylation of the presynaptic protein Munc18‐1. Mimicking constitutive phosphorylation of Munc18‐1 results in a drastic decrease in synaptic transmission. ERK‐mediated phosphorylation of Munc18‐1 ultimately leads to degradation by the ubiquitin–proteasome system. Conversely, preventing ERK‐dependent Munc18‐1 phosphorylation increases synaptic strength. CB1R‐ and mGluR2/3‐induced synaptic inhibition and depolarization‐induced suppression of excitation (DSE) are reduced upon ERK/MEK pathway inhibition and further reduced when ERK‐dependent Munc18‐1 phosphorylation is blocked. Thus, ERK‐dependent Munc18‐1 phosphorylation provides a major negative feedback loop to control synaptic strength upon activation of presynaptic receptors and during intense neuronal activity. Synopsis: ERK‐dependent Munc18‐1 phosphorylation contributes to synaptic depression upon activation of presynaptic CB1 or mGlu2/3 receptors and during intense neuronal activity. Munc18‐1 is a presynaptic ERK substrate in vivo . ERK produces synaptic depression by phosphorylating Munc18‐1. ERK‐dependent Munc18‐1 phosphorylation is a major factor in CB1R‐ and mGluR2/3‐induced presynaptic inhibition and depolarization suppression of excitation (DSE). Abstract : ERK‐dependent Munc18‐1 phosphorylation provides an important negative feedback loop in glutamatergic hippocampal neurons to regulate synaptic strength.